Scientific and theoretical aspects of effective use of production resources at industrial enterprises - Kham raeva Sayyora Nasimovna; Uzakov Mukhammadzhon Toshtemirovich (THE INNOVATION ECONOMY, 2026)
The article examines the scientific and theoretical foundations of the effective use of production resources at industrial enterprises. The conceptual framework is analyzed, and the main approaches to assessing and organiz ing the rational use of resources are highlighted. Particular attention is paid to modern trends in managing produc tion resources in the context of digitalization and technological transformation. The necessity of a systematic and comprehensive approach to resource saving as a factor in increasing the competitiveness of enterprises is substan tiated.